Investigation of 3D Printed Self-Sensing UHPC Composites Using Graphite and Hybrid Carbon Microfibers - Han Liu; Simon Laflamme; Bin Cai; Ping Lyu; Sri Sritharan; Kejin Wang (Sensors)
This paper explores the development of 3D-printed self-sensing Ultra-High Performance Concrete (UHPC) by incorporating graphite (G) powder, milled carbon microfiber (MCMF), and chopped carbon microfiber (CCMF) as additives into the UHPC matrix to enhance piezoresistive properties while maintaining workability for 3D printing. Percolation curves were established to identify optimal filler inclusion levels, and a series of compressive tests, including quasi-static cyclic, dynamic cyclic, and monotonic compressive loading, were conducted to evaluate the piezoresistive and mechanical performance of 29 different mix designs. It was found that incorporating G powder improved the conductivity of the UHPC but decreased compressive strength for both mold-cast and 3D-printed specimens. However, incorporating either MCMF or CCMF into the UHPC resulted in the maximum 9.8% and 19.2% increase in compressive strength and Young’s modulus, respectively, compared to the plain UHPC. The hybrid combination of MCMF and CCMF showed particularly effective in enhancing sensing performance, achieving strain linearity over 600 <semantics>με</semantics>. The best-preforming specimens (3G250M250CCMF) were fabricated using 3 wt% of G, 0.25 wt% of MCMF, and 0.25 wt% of CCMF, yielding a maximum strain gauge factor of 540, a resolution of 68 <semantics>με</semantics>, and an accuracy of 4.5 <semantics>με</semantics> under axial compression. The 3D-printed version of the best-performing specimens exhibited slightly diminished piezoresistive and mechanical behaviors compared to their mold-cast counterparts, yielding a maximum strain gauge factor of 410, a resolution of 99 <semantics>με</semantics>, and an accuracy of 8.6 <semantics>με</semantics>.